Disturbance rejection of a class of discrete-time multi-agent systems with pinning control. (11th November 2019) - Zhu, Qiuguo; Wu, Jun; Xiong, Rong
For discrete-time multi-agent systems with random switching nonlinear linking and exogenous disturbances, the disturbance rejection problem is studied and a sufficient condition is presented using the Lyapunov function. In an example of five agents with pinning control, the condition is adopted to optimize disturbance rejection. A numerical simulation shows that the optimization is effective.